2018
DOI: 10.21511/bbs.13(1).2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Ownership concentration, ownership identity, and bank performance

Abstract: This paper examines whether ownership concentration and certain type of ownership can affect the financial performance of Lebanese banks. It uses longitudinal data from the largest 35 Lebanese banks over the period 2009–2014 and employs the panel regression model. The empirical results show that ownership concentration and certain type of shareholders play an important role in the area of corporate governance in Lebanese banks. In particular, bank financial performance is positively associated with ownership c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
2
9
1
2
Order By: Relevance
“…Tan and Floros (2012) found that size had no effect on profitability in 101 banks in China. Meanwhile, Azoury et al (2018) found a negative effect between bank size on profitability in 35 banks in Lebanon. Likewise, Tan (2016) found that size had a negative effect on profitability in China and Javaid et al (2011) found a negative effect on the top 10 banks in India.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Tan and Floros (2012) found that size had no effect on profitability in 101 banks in China. Meanwhile, Azoury et al (2018) found a negative effect between bank size on profitability in 35 banks in Lebanon. Likewise, Tan (2016) found that size had a negative effect on profitability in China and Javaid et al (2011) found a negative effect on the top 10 banks in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…H1: The level of stability has a positive effect on the profitability of the BPRS Bank size (SIZE) is a proxy for the total assets owned by the bank (Azoury et al, 2018;Bougatef, 2017;Lee & Isa, 2017). Banks with large asset sizes tend to generate higher profitability because banks have more opportunities to diversify their profitable portfolios.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on foreign shareholder's value creation is still uncommon, especially in banking of developing countries like Indonesia. Among some examples are Johan et al [4], Batten et al [5], Dong et al [6], Ghosh [7], Bongini et al [8], Mori et al [9], Saif-Alyousfi et al [10], Agustin et al [11], Azoury et al [12], Shawtari [13], Basri et al [14], Kowaleski [15], and Rathnayake et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…Azoury et al [12] examines whether ownership concentration and a certain type of ownership can affect the financial performance of Lebanese banks. It uses longitudinal data from the most significant 35 Lebanese banks over the period 2009-2014 and employs the panel regression model.…”
Section: Introductionmentioning
confidence: 99%